SYSTEMATIC LITERATUR RIVIEW: ASESMEN KOMPETENSI MINIMUM (AKM) PADA DOMAIN BILANGAN - Afrina, Dian Meri; Pandra, Viktor; Fauziah, Anna (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2023)
The Minimum Competency Assessment (AKM) is an assessment designed to measure the literacy and numeracy skills needed by all students in developing themselves and actively participating in society and to prepare students to face the 21st century. The urgency of developing math learning outcomes assessment questions by teachers or educators it is deemed necessary to prepare students to face various literacy tests both on a national and international scale. This development resulted in a variation of 4 items for number content with ascientific, cultural, and personal context. The questions developed are in the form of multiple choice and complex multiple choice which ask for evidence/reasons in answering the questions. The questions developed are valid based on the validity of the content carried out by fellow teachers. This development provides a variety of AKM practice questions and initial ideas for developing meaningful assessment of learning outcomes in a particular context.